MEASURE THE IMPACT OF MAJOR STRUCTURAL CHNGES IN RURAL POVERTY FOR SELECTED ARAB COUNTRIES FOR THE PERIOD (1990-2010) - Aswan Abdul-Kadir Zaydan (Mesopotamia Journal of Agriculture)
ABSTRACT Correlation between the phenomena of structural changes and poverty comes from the structural change in developing countries That requires sharp turns in the paths of economic policies based on the package according to of Economic trends that differ from those adopted by the stste,and often,What comes from this The effects of economic changes is desirable to pay several categories of members of the community toward or below the poverty line, so it has targeted a research measure the effect of structural changes in rural poverty for the Arab States (Iraq, Egypt) for the period 1990-2010, through the dentification of structural variables that affect poverty, has represented the relationship between poverty index (the average per capita income) As a variable "follower " and has a determinant of the contribution of the agricultural output in GDP, agricultural labor, agricultural area, the proportion of agricultural labor / employment College, mechanical technology, capital invested in agriculture as independent variables, and through the identification of the inability of the agricultural sector in Iraq to accept the rapid growth of The difficulty of creating complete the process of structural transformation toward modify the structure of the agricultural sector, creating the problem of poverty to that of necessity require the development of the infrastructure in the countryside and increase and develop Agricultural research centers and support for agrarian reform and the establishment of appropriate and mainly in areas with strong social disparities and poverty and food insecurity as a means to encourage Get more broadly on the land, water and natural resources and control. As in Egypt to study results indicate that the percentage of the poverty rate for the Aasthen and severity of poverty and inequality in Distribution of poverty is concentrated in the villages than in urban areas, indicating the impact of economic reform and structural changes, so the study recommends that the followers of a number of measures to combat Poverty through the implementation of the three entrances is not independent from each other: the entrance to strengthen growth, human development entrance, the entrance of well-being.